The Systematisation of Survey Drawings: Identifying the Development of Morphological Awareness via Teaching Approaches - Gilberto Duarte Carlos; Alejandro López (Buildings)
The graphic replication of architectural examples has long been a prevalent pedagogical method, regardless of educational orientation. The critical reactivity of the mid-20th century, reinforced by ethnographic and anthropological tools, positioned vernacular architecture as a key educational resource—a process widely recognised and extensively studied in Portugal. This article examines the role of fieldwork and surveying techniques in architectural education, extending beyond geometric characterisation to encompass the recognition of technological principles and logics. Through the systematic application of decomposition/composition drawing exercises with first-year students over a decade, this study explores how structured graphical methodologies foster a deeper understanding of buildings, beyond their aesthetics. The findings indicate that perception skills constitute a crucial competence in architectural teaching curricula. The systematisation of hand drawing surveys, applying layering superimposing, is a valuable method to enhance these capacities practically. The results reinforce that early engagement with analytical drawing improves students’ ability to integrate conceptual and technical aspects in design, supporting a progressive transition to digital tools. Additionally, the results highlight the pedagogical value of vernacular studies in promoting adaptive and sustainable design thinking, reinforcing the need for a balanced approach that synthesises traditional and contemporary methodologies in architectural education.